The genetic variation rs6903956 in the novel androgen-dependent tissue factor pathway inhibitor regulating protein (ADTRP) gene is not associated with levels of plasma coagulation factors in the Singaporean Chinese. Issue 1 (December 2017) - Chang, Xuling; Chin, Hui-Lin; Quek, Swee-Chye; Goh, Daniel; Dorajoo, Rajkumar; Friedlander, Yechiel; Heng, Chew-Kiat
Abstract Background Genome-wide association study (GWAS) has reported that rs6903956 within the first intron of androgen-dependent tissue factor pathway inhibitor (TFPI) regulating protein (ADTRP ) gene is associated with coronary artery disease (CAD) risk in the Chinese population. Although ADTRP is believed to be involved in the upregulation of TFPI, the underlying mechanism involved is largely unknown. This study investigated the association of rs6903956 with plasma Factor VII coagulant activity (FVIIc) and fibrinogen levels, which are regulated by TFPI and are independent risk predictors for CAD. Methods We conducted the analysis in both Chinese adult (N = 309) and neonatal cohorts (N = 447). The genotypes of the rs6903956 single nucleotide polymorphism (SNP) were determined by the polymerase chain reaction restriction fragment length polymorphism method (PCR–RFLP). FVIIc and fibrinogen level were measured from citrated plasma. The association between rs6903956 and coagulation factors was tested by linear regression with adjustment for possible confounders. Analysis was carried out in adults and neonates separately. Results No significant association was observed between rs6903956 and plasma FVIIc nor fibrinogen levels with adjustment for age, gender, body mass index (BMI) and cigarette smoking in adults (P for FVIIc = 0.464; P for fibrinogen = 0.349). The SNP was also not associated with these two coagulation factors in the neonates (P for FVIIc = 0.579; P for fibrinogen = 0.359) after adjusting for gestational age, gender and birth weight. Conclusions SNP rs6903956 onADTRP gene was not associated with plasma FVIIc nor fibrinogen levels.